INFORMATION AND TECHNOLOGY FOR ADVANCED SOCIETY - Wibowo, Bambang Sri; Abdillah, Hasan; Lazuardi, Sofyan; Suprihandari, Miya Dewi (Transpublika Publisher, 2023)
Human resource management in community organizations and government entities in rural areas holds significant complexity and importance. Rural regions often serve as crucial supporting environments for surrounding urban centers, making effective human resource management pivotal for organizational success. This research aims to enhance Human Resource Management in Rural Areas Through Information Technology as an effort towards advanced societal development. By analyzing literature reviews, case studies, and real-world implementation examples, this study seeks to uncover how information technology can enhance recruitment, training, performance evaluation, and employee engagement in rural settings. The research highlights how technology can serve as a tool to improve operational efficiency, informed decision-making, and effective communication within rural community organizations and government entities. Thus, this study provides insights into how information technology can play a central role in supporting sustainable development and added value growth within rural communities. With a focus on successful technology implementation, this research can serve as a guide for rural community organizations and government entities to optimize their human resource potential. By combining technology with the unique needs of rural areas, this research can also inspire efforts towards broader sustainable development within advanced rural communities.